The role of five big personality traits and entrepreneurial mindset on entrepreneurial intentions among university students in Saudi Arabia - Al-Ghazali, Basheer M.; Shah, Syed Haider Ali; Sohail, M. Sadiq (Frontiers in Psychology, 2022)
The big five personality traits and entrepreneurial mindset (EM) are crucial individual-level elements that determine entrepreneurial intention (EI). This study examines the impact of big five personality traits and EM, on EI using the theory of planned behavior. Besides, this study examined the role of entrepreneurial self-efficacy (ESE) and attitude toward entrepreneurship (ATE) influences EI. To achieve the research objectives, a quantitative approach was used. Structural equation modeling (SEM) and path analysis were conducted using SmartPLS software. Data were collected from 270 respondents through online questionnaires. Findings of the study revealed that big five personality traits influence ESE and ATE which led to EI. Finally, the moderating role of entrepreneurial passion was also found to have strong effect on influence ESE and ATE. This study offers evidence and insights that academics, educators, and others involved in the creation or expansion of entrepreneurial knowledge can use as a reference point.